PENGARUH PENDAPATAN ORANG TUA TERHADAP PENINGKATAN PRESTASI BELAJAR SISWA KELAS X DI SMKN 2 JIWAN KABUPATEN MADIUN TAHUN 2011/2012 - Onnes Andong Kartiko (EQUILIBRIUM : Jurnal Ilmiah Ekonomi dan Pembelajarannya, 2013)
Family  represent  first  social  institute  which  recognized   by  child  and in this family  can be inculcated  attitudes  able to influence  growth  of child  hereinafter.  Family hold  responsible   to provide  fund for the requirement   of to education  of child. Family  ( old fellow) which  situation  of high economic  social will not finding  difficulties  many in fulfilling  requirement   of child  school,  differing  from  old fellow  is situation  of his eco- nomic  social  lower.  Target  of this  research  is  1. To know  the  condition   of earnings  of class student  old fellow  of X SMKN  2 Jiwan  Sub-Province  of Madiun  in the year lesson 2011 /20122.    To know  achievement   learn student  of X SMKN  2 Jiwan Sub-Province   of Madiun  in the year lesson  2011 /2012   3. To know  influence  of earnings  of old fellow to achievement   learn class of X SMKN 2 Jiwan  Sub-Province   of Madiun   School year 2011 / 2012.  Research  method  used  in this  research  is method  of diskriptif  with  its analysis desain  wear regresi.  Procedure   data collecting  bibliography   study and research  of field. Study bibliography   of writer  do by reading  various  erudite  compositions   or book  which concerning   theory  framework   is relefan  with  problem  of is studied.  Research   of field medium   to  obtain.get   primary   data  obtained  to through   documents   which  have  made available,  on the other hand data of sekunder  by Method  enquette  and observation  In this research,  enquette  used to know the condition  of economic  social of old fellow. Technics of data analysis  used by analysis  of statistic  with linear regresi modestly,  and to be tested its hypothesis   utilized  test of t or difference  of mean.  From  result  of research  by using Equation  of expressed  doubled  linear regression:   Equation  of the doubled  linear  regres- sion have positive  value  at konstanta  that is 54.26 expressing  that if earnings  of valuable old fellow  zero hence  achievement   learn  student  will be valuable  54.26.  54.26,  coeffi- cient  of Regresi  variable  of X is positive  equal  to 0.36, please  express  that  each;every earnings  of old fellow go up equal to one set of hence will cause improvement   or increase of achievement   learn equal to 0,36 one set of. Its meaning  of the influence  [is] influence which are positive.  Level of value ofThitung  equal to 29,02 signifikansi  0.05 with counter df equal to 1 and denominator   df equal to 30 is so that obtained  by value  of t-tabel  equal to  1.699.  Pursuant  to result  of the  comparison   seen  that thitung>ttabel   (29.02>1.699). Thereby  [job/activity]  hypothesis  (Ha)  expressing  that there is positive  influence  [among/ between]  earnings  of old fellow  old fellow to achievement  learn student  of SMK NEGERI 2 JIWAN"    accepted".